Characteristics and long-term prognosis of patients with rectal neuroendocrine tumors - Chi, Yihebali; Du, Feng; Zhao, Hong; Wang, Jin-Wan; Cai, Jian-Qiang (World journal of gastroenterology : WJG, 2014)
AIM:To analyze the clinicopathologic characteristics and prognostic factors of rectal neuroendocrine tumors.METHODS:The records of 48 patients with rectal neuroendocrine tumors who were treated at the Cancer Institute and Hospital,Chinese Academy of Medical Sciences,Beijing,from March 2004 to September 2009were retrospectively reviewed.The clinicopathological data were extracted and analyzed,and patients were followed-up by telephone or follow-up letter to determine their survival status.Follow-up data were available for all 48 patients.Uni-and multivariate Cox regression analyses were performed to determine the prognostic factors significantly associated with overall survival.RESULTS:The tumors occurred mostly in the middle and lower rectum,and the most prominent symptoms experienced by patients were hematochezia and diarrhea.The median distance between the tumors andthe anal edges was 5.0±2.257 cm,and the median diameter of the tumors was 0.8±1.413 cm.The major pathological type was a typical carcinoid tumor,which accounted for 93.8%(45/48)of patients.Tumor-nodemetastasis(TNM)stagesⅠ,Ⅱ,ⅢandⅣtumors accounted for 78.8%,3.9%,9.6%and 7.7%of patients,respectively.The main treatment method,in 72.9%(35/48)of patients,was transanal extended excision.The 1-,3-and 5-year survival rates of the whole group of patients were 100%,93.7%,and 91.3%,respectively.Univariate analysis showed that age(P=0.032),tumor diameter(P<0.001),histological type(P<0.001),TNM stage(P<0.001),and surgical approach(P=0.002)were all prognostic factors.On multivariate analysis,only the pathological type was shown to be an independent prognostic factor(HR=2.797,95%CI:1.676-4.668,P=0.004).CONCLUSION:In patients with rectal neuroendocrine tumors,TNM stage Ⅰ is the most common stage found,and lymph node or distant metastases are rarely seen.The pathological type of the tumor is an independent prognostic factor.